The effectivenes of blended learning model integrated independent learning on critical thinking - Erita, Selvia (CAHAYA PENDIDIKAN, 2023)
The goals and outputs of higher education education are to make students proficient in problem solving, creative, innovative and critical thinking. However, in reality students' critical thinking skills are still low. Therefore the aim of this research is: 1). Reveal the effectiveness of the blended learning model on students' critical thinking skills; 2). Knowing the interaction between blended learning models and learning independence in influencing critical thinking skills. Therefore, the design of this study is a mixed factorial between and within groups (Between Group-Within Group). 42 semester V students of IAIN Kerinci were sampled in this study. Critical thinking skills tests and questionnaires were used in this study which were analyzed quantitatively.  The results showed that the blended learning model was effective in influencing students' critical thinking skills with an average score of 72.3 while the control class's critical thinking skills had an average score of 60.45. In addition, based on the test between subjects effect model, a significance of 0.003 was obtained, Sig 0.05, meaning that there were differences in critical thinking skills between students using blended learning models and using conventional models. In addition, there is a significant interaction effect between independence and students' critical thinking skills.